1991
DOI: 10.2172/5585244
|View full text |Cite
|
Sign up to set email alerts
|

Engineering-scale test 4: In situ vitrification of toxic metals and volatile organics buried in INEL soils

Abstract: An engineering-scale in situ• vitrification (ISV) test was conducted on soils containing a mixture of buried waste materials expected to be present at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
4
2
0
Order By: Relevance
“…No measurableorganics were found at temperaturesbelow the 350_C isotherm. These results for volatile organics are consistentwith the results found 'inES-INEL-4 (Shade et al 1991) that indicated the volatile organics were in large part either transportedto the offgas system or destroyed.…”
supporting
confidence: 90%
“…No measurableorganics were found at temperaturesbelow the 350_C isotherm. These results for volatile organics are consistentwith the results found 'inES-INEL-4 (Shade et al 1991) that indicated the volatile organics were in large part either transportedto the offgas system or destroyed.…”
supporting
confidence: 90%
“…processed by the ISV treatment. The results obtained for the 1,1,2-trichloroethane, toluene, and xylene are quite consistent with those obtained in previous engineering-scale tests with these, or similar, volatile materials (e.g., Geosafe 1993;Shade et al 1991;and Timmerman 1986). It is interesting to note however, that the concentrations for these three simulants exhibit a peak at a depth about half-way down the treated zone &e., = 46 cm).…”
Section: Test Retrosdectivesupporting
confidence: 88%
“…The post-test soil samples taken around the block indicated concentrations below the detection limit for each of these chemicals. On the other hand, another test in the ES-INEL series, ES-INEM (Shade et al 1991), achieved success-rates comparable to those obtained in this ORNL-ESBW-6 test. The ES-INEL-4 test simulants were contained in a glass bottle to facilitate their placement in the target vitrificaiton zone, similar to what was done for the cresol staged in the ORNL-ESBW-6 test.…”
Section: Test Retrosdectivesupporting
confidence: 73%
“…A laboratorytest also establishedthe feasibility of using ISV to melt through unconsolidated soils and into an underlyinglayer of basalt (Shade et al 1991). In this test it was demonstratedthat upon reaching the underlying rock layer, temperatureswere sufficient to partially melt the basalt and fuse with the ISV melt.…”
Section: Appendix Figuresmentioning
confidence: 99%